The Role of Hope in Predicting Supported Employment Success. - Waynor, William R.; Gill, Kenneth J. (Journal of Rehabilitation)
Objective: This study tested whether hope would be a positive predictor of an employment outcome in supported employment (SE) programs for persons with serious mental illness (SMI). Method: A total of A/=105 participants with SMI receiving SE entered the study. Research staff met with the individuals at baseline and collected demographic information and data on hope and psychiatric symptoms. For the follow-up assessment at 6-months, data was collected on the participants, hope, psychiatric symptoms and employment activity. Results: An A/=82 met with study staff at the 6 month follow-up, 38% of these participants had attained an employment goal. Surprisingly, a point-biserial correlational analysis found that baseline hope was not a positive predictor of achieving an employment goal, but in fact was negatively correlated with attaining employment. Discussion: These findings suggest that greater hope may not be a predictor of employment at the outcome level for this population.